Emerging Adults’ Consideration of their Future General and Colorectal-Specific Cancer Risk - Jackie Knight Wilt PhD; Maria D. Thomson PhD (Cancer Control)
Introduction Colorectal cancer (CRC) has a lengthy cellular mutation period and early onset (EOCRC) is linked to lifestyle-related factors. Primary prevention approaches earlier in the life course are needed. Emerging adulthood (age 18-25) is a critical stage for shaping health trajectories, and future orientation influences health behavior decisions. Little is known about emerging adults’ consideration of future cancer risk (CFC-Cancer), or perceived CRC risk. This study characterizes emerging adult CFC-Cancer, perceived CRC risk, and how they relate to EOCRC lifestyle related factors and cancer prevention behaviors. Methods We conducted a cross-sectional survey of college students at a public university. Measures included demographics, stress, family cancer history, and CRC knowledge. Previously validated measures for diet, sedentariness, smoking, alcohol consumption, and stress management assessed adherence with lifestyle prevention guidelines. HPV vaccination and skin checks appraised cancer prevention. Outcomes included perceived CRC risk (0%–100%) and CFC-Cancer adapted scale. Adjusted linear regression models examined CFC-Cancer and perceived CRC risk predictability. Results The sample (N = 282) mean age was 20 years, 77% were female, 40% were White, and 67% had family cancer history. CRC knowledge μ = 14, and current stress was moderate. 18% completed both cancer prevention behaviors, and protective lifestyle behavior scores ranged between 2-15, μ = 8. Perceived CRC risk = 28%, and CFC-Cancer was moderate (μ = 61). CFC-Cancer model included significant predictors of GPA, CRC knowledge, and lifestyle health behavior score, while Perceived CRC Risk model included age and being employed. Conclusion Emerging adults overestimate CRC risk but also have moderate CFC-Cancer. Accurate CRC knowledge provided to this age group may help redirect CRC health trajectories through integration of EOCRC protective lifestyle health behaviors and sustaining them into adulthood.